Health promotion of families of deaf children - Mirna Albuquerque Frota; Larissa Cipião Gurgel do Amaral; Caroline Soares Nobre; Priscilla Mayara Estrela Barbosa (Universidade de Fortaleza, 2012)
Objective: To investigate the impact of hearing loss in the family dynamics of the deaf child; identify the family's knowledge about deafness, understand how parents experience the diagnosis and treatment of child with hearing impairment. Methods: The study has aqualitative approach developed at the Center for Integrated Medical Care - NAMI, attached to the University of Fortaleza - UNIFOR located in Fortaleza - CE, Brazil. The participants were six mothers of children with hearing impairment. Data collection was carried outthrough participant observation and semi-structured interview. The Thematic Analysis of Bardin was used for processing the data. Results: After coding, some categories emerged from the discourse: Misinformation of Hearing Loss; impact of the discovery of hearingloss, caregivers and facilitators of the development of the deaf children. Conclusion: The birth of a deaf child alters the previous family balance, causing specific problems, such as the communication barrier, whose solution is related to how to handle the situation. Itis necessary to promote changes, emphasizing the involvement of caregivers and loved as facilitators of deaf child's development. In Phonoaudiology, this attitude represents discovering new ways to identify the need for the subject, which requires strategies thatvalue their opinion, allowing the expression of expectations, perceptions, representations and feelings.